Traditional Malay building as-built drawings reproduction using building information modelling - Mustafa, Muhammad Hadi; Ali, Maisarah; Mohamad Suhaimi, Mohamad Saifulnizam; Hashim, Khairusy Syakirin Has-Yun; Mohd Ismail, Kamsiah (2018)
In conserving historical structures such as the traditional Malay buildings, conservators often face problems of insufficient reliable references before executing the conservation work. Most of the documents are often not available because they are disposed, missing or outdated. As-built drawings are among the documents. As-built drawings are important for conservation because it shows useful information such as the layout of the historical building. Because of this, the drawings should be referred before any conservation plans are made. The objective of this paper is to show how tools such as laser scanner and Building Information Modelling (BIM) software can be used to re-produce the often lost as-built drawing accurately. This paper employs an explorative approach where a traditional Malay palace is adopted as a case study to prove this. The application of integrating these two tools to produce as-built drawings of the historical building shows that the effort is able to simultaneously produce a 2D as-built drawings and 3D models successfully by a single work. By having data from laser scanning, it also eliminates the need to have frequent site visits and the details of the building can be further explored effortlessly from workstations. It is hoped that this revolutionary tools will find a wider audience and our invaluable information about national’s historical assets can be appreciated.